METHODOLOGICAL ANALYSIS OF THE CONTENT AND TECHNOLOGIES OF TEACHING ORIGINAL LITERARY TEXTS AS A MEANS OF DEVELOPING PROFESSIONAL COMPETENCIES OF FUTURE ENGLISH LANGUAGE TEACHERS - O'lmasova Nodira Rustamjon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes the methodological aspects of using original literary texts in the development of professional competencies of future English language teachers. The study examines the role of literary texts in the content of teaching, the application of modern pedagogical technologies, and the possibilities of a competency-based approach. The results of the analysis demonstrate that original literary texts serve as an effective tool for developing linguistic, communicative, intercultural, and methodological competencies. The article contributes to improving the effectiveness of teacher education in the field of English language teaching.